Pengaruh Promosi Digital Dan Citra Destinasi Wisata Terhadap Keputusan Berkunjung Wisatawan Pada Pantai Rio By The Beach Kalianda Lampung Selatan - Hepiana Patmarina; Nur Annisa (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2026)
This study aims to explore the impact of digital promotion and destination image on tourists' visiting decisions at Rio by The Beach, Kalianda, South Lampung, employing the Theory of Planned Behavior as the theoretical foundation. A quantitative approach was utilized, involving 100 tourists as the sample determined through specific sampling techniques. Data were collected via questionnaire surveys, while data analysis was conducted using multiple linear regression with SPSS software. The results indicate that digital promotion and destination image, both partially and simultaneously, have a positive and significant influence on visiting decisions. These findings suggest that effective digital marketing strategies and good management of the destination's physical and non-physical image are crucial factors in attracting tourists. This study recommends a synergy between engaging social media content and the maintenance of destination facilities to ensure sustainable tourism visits.Keywords: Digital Promotion, Destination Image, Visiting Decision, Tourism